Effect of the application of organic materials on the physical properties of an Inceptisol - Alvarez-Herrera, Javier Giovanni; Hernández-Pachón, Pablo Sebastián; Molano-Díaz, Julián Mauricio (Revista de Ciencias Agrícolas, 2025)
Soil agricultural production is vital for ensuring people's nutrition. However, improper use has led to soil degradation, reducing its productive capacity. Adding organic matter improves the physical properties of soil. This study aimed to evaluate how incorporating organic materials affects certain soil physical properties on the 'La María' farm. A completely randomized design was used with five treatments: applying raw rice husk, toasted rice husk, chicken manure, liquid organic fertilizer, and a control. There were no significant differences observed in soil penetration resistance (PR), a property linked to soil compaction and root growth potential, with values ranging from 500 to 1250 kPa at depths of 2.5 to 17.5 cm. PR also showed temporal variation depending on rainfall. Organic material additions reduced apparent bulk density from 1.63 to 1.45 g/cm³; however, this effect is temporary, and materials should be reapplied about every six months. All tested organic materials promoted soil particle aggregation, increasing it from 23.28 to 5.23 mm. Higher application rates of these materials are recommended to achieve a greater impact on the soil's physical properties.